EFFECT OF PLANT PRUNING AND TOPPING ON YIELDING OF EGGPLANT IN UNHEATED FOIL TUNNEL - Halina Buczkowska (Acta Scientiarum Polonorum: Hortorum Cultus, 2010)
Due to strong eggplant growth and the formation of large vegetative weight quantities in growing under glass and foil it was deemed useful to conduct studies on the effect of pruning intensity on yielding of this vegetable in rooms. The aim of the foregoing studies was to demonstrate the effect of plant pruning and topping manner on yield quantity and earliness. The experiment was conducted in the years 2001–2003. The study objects were the plants of ‘Epic F1’ cultivar. Eggplant was grown in rigid foil cylinders of the capacity of 10 dm3 in the peat substrates. The plants were trimmed, managing for one, two, three, four, five, six guiding shoots and in the natural form, without trimming. Topping cut was performed in each combination after the first fruit harvest. The experiment was established and conducted as a two-factor one, in accordance with a complete randomization system: A – pruning method (a = 7), B – topped and non-topped plants (b = 2). Each combination of the examined factors was represented by 20 plants (experimental units). A significant effect of pruning intensity on the quantity and earliness yielding was demonstrated. The highest marketable fruit yield was obtained from plants managed for two (3.82 kg.m-2), three (3.98 kg.m-2), and four (3.87 kg.m-2) guiding shoots. Managing for one guiding shoot significantly decreased the total and marketable fruit number. The highest early yield was collected from plants managed for one and two guiding shoots. A single topping cut performed after the first fruit harvest did not affect marketable yield and marketable fruit number.